Effect of Surface Stabilizers on the Optical Properties of ZnSe/ZnS:Mn/ZnS Nanocrystals - Thi Diem Bui; Quang Liem Nguyen; Nguyen Van Cuong; Trong Tang Nguyen (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
In this study, we produced nano-sized, spherical ZnSe/ZnS:Mn/ZnS in a non-toxic aqueous solvent with surface stabilizers such as 3-mercaptopropionic acid (MPA), polyethylene glycol (PEG), and starch. These surface stabilizers aid to prevent agglomeration and passivation, thereby stabilizing the nanoparticle surface. ZnSe/ZnS:Mn/ZnS nanocrystals (NCs) are cubic in structure. Changing the surface stabilizer and doping Mn metal does not alter the structure of the ZnSe base material, but it boosts fluorescence efficiency by 2.2 - 3.9 times. The fluorescence efficiency of ZnSe/ZnS:Mn/ZnS MPA NCs using MPA stabilizer is 73.95%, which is higher than the fluorescence efficiency of ZnSe/ZnS:Mn/ZnS Starch NCs (57.35%) using Starch stabilizer and higher than the fluorescence efficiency of ZnSe/ZnS:Mn/ZnS PEG NCs (41.72%) using PEG stabilizer. ZnSe/ZnS:Mn/ZnS MPA NCs are originally assessed for their potential use in biomedical applications. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).